INTERNATIONAL BANKING RISK MANAGEMENT IN GLOBALIZATION CONDITIONS - David I. Filippov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The issue of global cash flows on world markets is becoming extremely important today. The article deals with the problem of supervising and regulating commercial banks in the US, Japan, the EU and Great Britain. The author provides indicators of finance efficiency of large banks of industrialized countries and BRICS. Principle barriers preventing higher efficiency of credit organizations functioning and arranging banking market with higher liquidity were described. The author proposes key provisions of the strategy aimed at the development of the national system of managing bank risks and methods of enhancing the information base in order to improve bank risk management.